Strategi Manajemen Perubahan Untuk Meningkatkan Minat Pelanggan Dengan Memanfaatkan Teknologi Di Café Greete Lubeg - Sari, Shinta Permata; Dasril, Dasril; Florella, Maria; Rafine, Zhilan Syabrilla Permata; Putra, Ramdhani Bayu (CV. ITTC INDONESIA, 2024)
This Community Service aims to find out the Change Management Strategy to Increase Customer Interest by Utilizing Technology at Café Greete Lubeg. Technology plays a crucial role in facing these challenges. The use of technology can not only improve operational efficiency, but also provide a better experience for customers. From online ordering systems, loyalty apps, to social media for promotions, the use of technology can create closer interactions between cafes and customers. Change management at Greete Café aims to ensure businesses are able to adapt to evolving market dynamics, technology, and customer needs.